Proceedings of 2nd International Electronic Conference on Medicinal Chemistry 2016
DOI: 10.3390/ecmc-2-a019
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Antiviral Activity of Fluorinated Heterocyclic Compounds</strong>

Abstract: Nucleoside analogues have a special place among the most effective antiviral drugs and the study of fluorinated nucleoside sugars has led to the development of novel promising chemotherapeutic agents. Our work is dedicated to the determination of cytotoxicity and antiviral activity towards HSV-1, HSV-2 and HAdV5 of such modified nucleosides. Human adenovirus (HAdV) are ubiquitous infectious DNA viruses possessing a broad spectrum of pathogenicity. More than 60 HAdV serotypes have been identified that are respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Biliavska and coworkers synthesized fluorinated 1,2,3-triazole 164 ( Supplementary Table S1 ) ( Biliavska et al, 2017 ) and reported them as novel promising chemotherapeutic agents. Using MTT test at concentrations of 50 μg/ml, it was observed that 164 suppressed HSV-1/US reproduction by 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Biliavska and coworkers synthesized fluorinated 1,2,3-triazole 164 ( Supplementary Table S1 ) ( Biliavska et al, 2017 ) and reported them as novel promising chemotherapeutic agents. Using MTT test at concentrations of 50 μg/ml, it was observed that 164 suppressed HSV-1/US reproduction by 50%.…”
Section: Introductionmentioning
confidence: 99%